Combined radiographic and ultrasonographic assessment of postoperative diaphragmatic dysfunction after cardiac surgery: incidence, predictors, and clinical outcomes — a prospective cohort study - Mohamed Khaled Elnagar; Mohamed Moustafa Abdelaal; Wael Mohamed Elfeky; Mohamed Gamal Shaat; Amr Ahmed Ettish (The Cardiothoracic Surgeon, 2026)
Abstract Background Reported incidences of postoperative diaphragmatic dysfunction vary widely, largely because diagnostic criteria differ and preoperative imaging is seldom available; whether anatomical elevation, contractile impairment, or their combination carries clinical consequence is undefined, and the reproducibility of any composite definition has not been established. We prospectively studied 169 adults undergoing cardiac surgery, pairing standardised pre- and postoperative chest radiography with quantitative diaphragmatic ultrasonography performed in every patient, to determine the incidence, reliability, predictors and clinical consequences of dysfunction defined as new anatomical elevation combined with contractile failure. Results Combined dysfunction occurred in 18.3% of patients, isolated radiographic elevation in 3.6% and isolated ultrasonographic impairment in 10.7%. Measurement reliability was high (intra-observer ICC 0.886–0.952; inter-observer 0.832–0.901), and the combined criterion reproduced the phenotype far more consistently than ultrasonography alone (intra- and inter-observer agreement 100% and 96.7% versus 83.3% and 70.0%). Redefining dysfunction against each patient’s own preoperative baseline reproduced the classification in 98.2% of patients (κ = 0.938), supporting the literature-derived thresholds in this population. Coronary grafting with left internal mammary artery harvesting — a combined exposure these data cannot partition — was independently associated with dysfunction (adjusted odds ratio 3.95, 95% confidence interval 1.32–11.82), as was diabetes mellitus (3.09, 1.26–7.56); dysfunction was left-sided in 28 of 31 cases. After adjustment, affected patients required 1.45 times longer mechanical ventilation (95% CI 1.06–1.98) and 1.41 times longer hospitalisation (1.13–1.76), with a smaller, non-significant difference in intensive care stay; in absolute terms these amounted to approximately one additional hour of ventilation and one additional day in hospital. Prolonged ventilation and hospitalisation were concentrated in the combined-criterion group, and 89.7% of affected survivors regained normal function by three months. Conclusions Anchoring radiography to an individual preoperative baseline and requiring ultrasonographic confirmation identifies diaphragmatic injury more specifically, and more reproducibly, than either modality alone, and its thresholds are concordant with a within-patient definition. Mammary-artery grafting and diabetes mark mechanical–ischaemic and metabolic susceptibility, supporting phrenic-protective technique and perioperative glycaemic optimisation as testable interventions.